Flicker Regularity Is Crucial for Entrainment of Alpha Oscillations - Notbohm, Annika; Herrmann, Christoph S. (Frontiers in Human Neuroscience, 2016)
Previous studies have shown that alpha oscillations (8-13 Hz) in human electroencephalogram (EEG) modulate perception via phase-dependent inhibition. If entrained to an external driving force, inhibition maxima and minima of the oscillation appear more distinct in time and make potential phase-dependent perception predictable. There is an ongoing debate about whether visual stimulation is suitable to entrain alpha oscillations. On the one hand, it has been argued that a series of light flashes results in transient event-related responses (ERPs) superimposed on the ongoing EEG. On the other hand, it has been demonstrated that alpha oscillations become entrained to a series of light flashes if they are presented at a certain temporal regularity. This raises the question under which circumstances a sequence of light flashes causes entrainment, i.e. whether an arrhythmic stream of light flashes would also result in entrainment. Here, we measured detection rates in response to visual targets at two opposing stimulation phases during rhythmic and arrhythmic light stimulation. We introduce a new measure called ‘behavioral modulation depth’ to determine differences in perception. This measure is capable of correcting for inevitable artifacts that occur in visual detection tasks during visual stimulation. The physical concept of entrainment predicts that increased stimulation intensity should produce stronger entrainment. Thus, two experiments with medium (Experiment 1) and high (Experiment 2) stimulation intensity were performed. Data from the first experiment show that the behavioral modulation depth (alpha phase-dependent differences in detection threshold) increases with increasing entrainment of alpha oscillations. Furthermore, individual alpha phase delays of entrained alpha oscillations determine the behavioral modulation depth: the largest behavioral modulation depth can be found if targets presented during the minimum of the entrained oscillation are compared to those presented during the maximum. In the second experiment stimulation with higher light intensity during both rhythmic and arrhythmic stimulation lead to an increased behavioral modulation depth, supposedly as a consequence of stronger entrainment during rhythmic stimulation. Altogether, our results reveal evidence for rhythmic and arrhythmic visual stimulation to induce fundamentally different processes in the brain: we suggest that rhythmic but not arrhythmic stimulation interacts with ongoing alpha oscillations